El rol del defensor de los derechos y garantías constitucionales de los niños y niñas y adolescentes - Aguirre Bermeo, Mayra Claribel (2013)
This thesis, on the theme "The role of the defender of the rights and constitutional guarantees of children and adolescents", the different chapters relate relevant aspects of the topic under investigation. In the introduction, an analysis of the failure of the defense of children and adolescents, on the critical, noted the reality on the lack of defense to children and adolescents, says the general and specific objectives, the hypothesis, independent and dependent variables and resources are detailed. The theoretical framework is based, the Doctrinal, Jurisprudential, Legislation regarding the object of study is also presented comparative law which refers to different countries in which we have implemented the Ombudsman for children and adolescents. In the methodology, determine the methods, the techniques applied in the field, by applying surveys to citizens of Canton La Maná, and interview with a judge, with such results tabulation was made, data processing and analysis was developed reporting research and hypothesis testing. The proposed legal reform to art.8 Increased by subsection of the Code of Children and Adolescents. Finally conclusions and recommendations are detailed